Spread of Recombinant DNA by Roots and Pollen of Transgenic Potato Plants, Identified by Highly Specific Biomonitoring Using Natural Transformation of an Acinetobacter sp. - de Vries, Johann (American Society for Microbiology, 2003)
Transgenic potato plants with the nptII gene coding for neomycin phosphotransferase (kanamycin resistance) as a selection marker were examined for the spread of recombinant DNA into the environment. We used the recombinant fusion of nptII with the tg4 terminator for a novel biomonitoring technique. This depended on natural transformation of Acinetobacter sp. strain BD413 cells having in their genomes a terminally truncated nptII gene (nptII′; kanamycin sensitivity) followed by the tg4 terminator. Integration of the recombinant fusion DNA by homologous recombination in nptII′ and tg4 restored nptII, leading to kanamycin-resistant transformants. DNA of the transgenic potato was detectable with high sensitivity, while no transformants were obtained with the DNA of other transgenic plants harboring nptII in different genetic contexts. The recombinant DNA was frequently found in rhizosphere extracts of transgenic potato plants from field plots. In a series of field plot and greenhouse experiments we identified two sources of this DNA: spread by roots during plant growth and by pollen during flowering. Both sources also contributed to the spread of the transgene into the rhizospheres of nontransgenic plants in the vicinity. The longest persistence of transforming DNA in field soil was observed with soil from a potato field in 1997 sampled in the following year in April and then stored moist at 4°C in the dark for 4 years prior to extract preparation and transformation. In this study natural transformation is used as a reliable laboratory technique to detect recombinant DNA but is not used for monitoring horizontal gene transfer in the environment.